Seeing Divine Speech : Sensory intersections in Luke's Birth Narrative and Beyond - Wilson, Brittany E.
This article explores how divine discourse in Luke-Acts intersects with the sense of sight. Divine discourse is never simply heard, for speech crosses sensory lines and blurs any clear demarcation between the verbal and the visual. In exploring these sensory intersections, I begin with Luke's arguably most logocentric section - the birth narrative - and discuss the divine-human encounters that occur here. After this analysis of the epiphanies in Lk. 1 -2, I then trace how the patterns concerning sight and its overlaps with divine speech are amplified later in Luke-Acts. Beyond the birth narrative, Luke increases the importance of the visual in divine - human encounters, mainly with respect to (1) the role of sight epiphanies, (2) the function of sings in facilitating faith and (3) the motif of revelation and hiddeness. Indeed, we shall see that, for Luke, there is something important to 'seeing' divine speech.
Keywords: Sight; Sensory Criticism; Epiphany